MANAGEMENT OF STARTING PRICES FORMING FOR TIMBER DURING AUCTION TRADE IN UKRAINE - Muraviov, Yurii (Forestry Education and Science: Current Challenges and Development Prospects, 2026)
The mechanisms for managing the pricing process for round timber in auction trade in Ukraine are studied. Particular attention is paid to the role of electronic trading platforms in ensuring transparency and competitiveness of bidding. The need to improve methodological approaches to establishing the initial value of lots is substantiated to prevent dumping and stimulate rational forest use. Recommendations are proposed for optimizing the pricing strategy for state forestry enterprises in order to increase their economic efficiency in conditions of martial law and post-war recovery.